Relationship between Perceived Academic Stress and Academic Performance among Students in Primary Teacher Training Colleges in Central Region, Kenya - Muema, Elizabeth Ndinda; Muola, James; Muriungi, Pamela (Journal of Humanities And Social Science, 2020)
This study was designed to determine the relationship between Perceived Academic Stress and Academic Performance among students in teacher training colleges in central region in Kenya. It was guided by Transactional theory and adopted descriptive survey design. The study targeted all second year students in Public Primary Teacher Training Colleges in central region in 2019. Purposive sampling was used to select central region, second years‟ students and deans of curriculum. Simple random sampling was used to select 197 students and 20 lecturers and stratified sampling to select gender. The instrument used to collect was perceived academic stress scale. Academic Performance was inferred from the students mean grade obtained from the Mid-course examinations Means and standard deviations were used to describe the data while. quantitative data was analyzed using SPSS version 26. The relationships among the variables was examined using Pearson Product Moment Correlation Coefficient and regression analysis was used to measure the strength of the relationship. On the overall perceived academic stress was found to have significant negative effect on academic performance (r=0.-68, p< 0.01), n=197) Academic performance was found to negatively correlated to specific measures of perceived academic stress as follows, academic stressors (r =-0.71,p<,0.01),intrapersonal stressors (r =-0.61,p,<0.001),Social stressors(r=-0.55,p<,0.01), Environmental stressors(r=-0.29,p,<0.01)with the subscales having significant negative correlations. Perceived academic stress had a significant predictive weight on academic performance (F, 4,192) =58.5,p, <0.05) with only academic stressors predicting academic performance. From the findings it was recommended that educators and administrators should ensure that Students support services like guidance and counselling are strengthened, and is important for the colleges to develop intervention programs to buffer the negative impact of stressful environments and enhance positive coping strategies which enhance academic performance
Keywords: Stress; Academic stress; Academic stressors; environmental stressors; social stressors; intrapersonal stressors Performance; Primary Teacher training colleges